Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

First report of pseudopithomyces mori causing leaf spot on mandarin in Italy - Ornella Incerti; Mario Masiello; Marika Desopo; Nancy Terlizzi; Rosalba Latrofa; Asia Mostacci; Lucia Convertini; Paola Ferrante; Antonio Ippolito; Simona Marianna Sanzani (Journal of Plant Pathology, 2024)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Tuning of Muscle Synergies During Walking Along Rectilinear and Curvilinear Trajectories in Humans - Noelia Chia Bejarano; Alessandra Pedrocchi; Antonio Nardone; Marco Schieppati; Walter Baccinelli; Marco Monticone; Giancarlo Ferrigno; Simona Ferrante (Annals of Biomedical Engineering, 2017)

Neuro-Mechanics of Recumbent Leg Cycling in Post-Acute Stroke Patients - Emilia Ambrosini; Cristiano De Marchis; Alessandra Pedrocchi; Giancarlo Ferrigno; Marco Monticone; Maurizio Schmid; Tommaso D’Alessio; Silvia Conforto; Simona Ferrante (Annals of Biomedical Engineering, 2016)

Omega-3 fatty acid supplementation reduces one-year risk of atrial fibrillation in patients hospitalized with myocardial infarction - Alejandro Macchia; Simona Monte; Fabio Pellegrini; Marilena Romero; Daniel Ferrante; Hernán Doval; Antonio D’Ettorre; Aldo Pietro Maggioni; Gianni Tognoni (European Journal of Clinical Pharmacology, 2008)

Antiangiogenic, antitumoural and antimetastatic effects of two distamycin A derivatives with anti-HIV-1 Tat activity in a Kaposi's sarcoma-like murine model - Laura Possati; Diana Campioni; Francesco Sola; Luciana Leone; Luigi Ferrante; Cecilia Trabanelli; Marina Ciomei; Marco Montesi; Romina Rocchetti; Simona Talevi; Stefano Bompadre; Antonella Caputo; et al. (Clinical & Experimental Metastasis, 1999)